Kudoa dianae sp. n. (Myxosporea: Multivalvulida), a new parasite of bullseye puffer, Sphoeroides annulatus (Tetraodontiformes: Tetraodontidae) - Dyková, Iva; Fajer Avila, Emma Josefina; Fiala, Ivan (Folia parasitologica, 2002)
A new multivalvulid myxosporean species, Kudoa dianae sp. n., is described from bullseye puffer, Sphoeroides annulatus (Jenyns) (Tetraodontiformes: Tetraodontidae). Plasmodia develop in extramuscular sites, in the wall of oesophagus and less frequently on mesenteries. Mature spores can reach lumen of the digestive tract directly by disruption of plasmodial wall or via macrophage transport to the oesophageal epithelium. New species is characterised by morphology of spores and by the complete sequence of SSU rRNA gene that differs from all hitherto known sequences of Kudoa species. Spore morphology (moderate-sized, simple non-ornate spores, quadrate in apical view) clusters with that of Kudoa scienae, K. cerebralis, K. chilkaensis, K. leiostomi, K. finduli, K. cascasia and K. ovivora. Analysis of phylogenetic relationships (using SSU rRNA gene sequences) among five Kudoa species, the molecular data of which are available thus far, revealed that K. dianae is distinguishable from these five species and that its closest relation is with K. miniauiriculata.
Keywords: protozoální DNA; Tetraodontiformes; Fish Diseases; fylogeneze; Phylogeny; Eukaryota; ribozomální DNA; molekulární sekvence - údaje; protozoální infekce zvířat; DNA, Protozoan; RNA, Ribosomal; Animals; Protozoan Infections, Animal; Microscopy, Electron, Scanning; RNA ribozomální; zvířata; nemoci ryb; Spores; spory; Molecular Sequence Data; DNA, Ribosomal; mikroskopie elektronová rastrovací